A hydrophobic bio-adsorbent synthesized by nanoparticle-modified graphene oxide coated corn straw pith for dye adsorption and photocatalytic degradation. Issue 27 (5th December 2020) - Chen, Juan; Liu, Shanshan; Ge, Heyi; Zou, Yu
ABSTRACT: A novel bio-adsorbent was prepared from corn straw pith (CSP), graphene oxide (GO) and TiO2 through one-step synthesis for adsorption and photocatalytic reduction of dyes. CSP and GO acted as stent and coat, respectively. TiO2 nanoparticles attached on the surface of the adsorbent played a role in the degradation of dyes and endowed the adsorbent with hydrophobicity. When the loading of GO and TiO2 were 5 and 20 wt.% respectively, the adsorbent had quite an ideal structure and satisfactory removal efficiency. There were an electrostatic attraction, hydrophobic and π – π interactions in the process of adsorption. The pseudo-second-order and the Langmuir model described the adsorption behaviour well. The dyes loaded on the adsorbent could be degraded by irradiation with ultraviolet light (UV). After five cycles, the removal efficiency of malachite green, methylene blue and rhodamine b by CSP-5GO-20TiO2 decreased by 3.77%, 23.89% and 32.01%, respectively. Therefore, the bio-adsorbent has the advantages of economy, environmental protection, and the concept of sustainable development. GRAPHICAL ABSTRACT: UF0001